Sobre la epigrafía romana de Numancia (Garray, Soria) ¿Una producción local? (Salduie, 2025)
An update of the information available on Numantine epigraphy has been presented in a previous publication. The recent discovery of a new inscription at the Numantia Site-Museum is now the starting point for an exhaustive review of the epigraphs linked to this settlement, both those recovered at the site itself and those found in surrounding areas. From this analysis, it has been possible to identify a series of patterns and morphological characteristics shared by these inscriptions, which seem to indicate the differentiation of at least two officinae specialised in the epigraphic production linked to this enclave, which have been named Numancia I and Numancia II.
Keywords: Numancia; Inscription; Offcinae; Hispania Citerior Tarraconensis; Local production